2009
DOI: 10.1021/bi802141y
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of HIV-1 Integrase Display a Two-Step, Slow-Binding Inhibition Mechanism Which Is Absent in a Drug-Resistant T66I/M154I Mutant

Abstract: Two-metal binding HIV-1 integrase inhibitors (INIs) are potent inhibitors of HIV-1 in vitro and in patients. We report here for the first time the kinetics of inhibition of integrase-catalyzed strand transfer. First, the IC(50) values for each of six structurally distinct INIs decreased when a preincubation was included: S-1360 (1.3 microM vs 0.12 microM), L-731,988 (130 nM vs 9 nM), L-870,810 (130 nM vs 4 nM), raltegravir (300 nM vs 9 nM), elvitegravir (90 nM vs 6 nM), and GSK364735 (90 nM vs 6 nM). When reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Streptavidin-coated scintillation proximity assay (SPA) imaging beads were purchased from PerkinElmer (Boston, MA). Full-length HIV-1 BH10 wild-type and mutant IN enzymes were expressed and purified as described previously (19) with or without 2-mercaptoethanol in the lysis and extraction buffers. Site-directed mutagenesis was used to make mutations in the wild type HIV-1 BH10 IN sequence (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptavidin-coated scintillation proximity assay (SPA) imaging beads were purchased from PerkinElmer (Boston, MA). Full-length HIV-1 BH10 wild-type and mutant IN enzymes were expressed and purified as described previously (19) with or without 2-mercaptoethanol in the lysis and extraction buffers. Site-directed mutagenesis was used to make mutations in the wild type HIV-1 BH10 IN sequence (41).…”
Section: Methodsmentioning
confidence: 99%
“…Of note, biochemical studies have suggested that binding of INIs to HIV-1 IN proceeds by a two-step mechanism with a slow second step, and mutations that increase resistance may alter this mechanism (19,32). In addition, fast INI dissociation has been proposed to contribute to INI resistance with the N155H, T66I, and Q148R IN substitutions (14,23).…”
mentioning
confidence: 99%
“…Localization of these STIs within the active site of the surrogate PFV intasome (6,19) has provided significant structural insights into their mechanisms for inhibiting strand transfer and the development of drug resistance. STIs also have varying capabilities to kinetically "trap" the HIV SC (10,20,21), apparently due to slow dissociation properties of the STI (22)(23)(24)(25)(26). The HIV IN STIs appear to trap SC by making contacts with both IN and DNA, as shown for the PFV intasome (6,19).…”
mentioning
confidence: 99%
“…INSTIs interact with the intasome in two distinct ways; they bind the two Mg 2ϩ ions in the active site and they displace the terminal adenosine of the integrating DNA strand, allowing a halobenzyl moiety to stack with the base of the penultimate cytosine (28). Kinetic data indicate a two-step binding mechanism (22,37), suggesting that Mg 2ϩ binding and cytosine stacking could be decoupled and proceed at different rates. These structures are particularly exciting because they reveal that INSTIs interact extensively with highly conserved elements in and around the active site and that INSTI binding may require less direct protein contact than do those of other types of anti-HIV drugs.…”
mentioning
confidence: 99%